2017
DOI: 10.1097/psy.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

Low Control and High Demands at Work as Risk Factors for Suicide: An Australian National Population-Level Case-Control Study

Abstract: It seems that adverse experiences at work are a risk factor for male suicide while not being associated with an elevated risk among females. Future studies on job stressors and suicide are needed, both to further understand the biobehavioral mechanisms explaining the link between job stress and suicide, and to inform targeted prevention initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
2
26
1
4
Order By: Relevance
“…These psychosocial stressors have been identified as risk factors for a large number of common mental health problems, chronic illnesses and mortality [2628]. Even more relevant to the current study, a recent publication using a population-level case-control design identified low control and high demands as key risk factors for suicide among employed males [29]. This corroborates past research from other countries [3035] and highlights these as additional factors raising the risk of suicide among workers in these occupations.…”
Section: Discussionmentioning
confidence: 96%
“…These psychosocial stressors have been identified as risk factors for a large number of common mental health problems, chronic illnesses and mortality [2628]. Even more relevant to the current study, a recent publication using a population-level case-control design identified low control and high demands as key risk factors for suicide among employed males [29]. This corroborates past research from other countries [3035] and highlights these as additional factors raising the risk of suicide among workers in these occupations.…”
Section: Discussionmentioning
confidence: 96%
“…If control over a job requires a level of understanding in terms of requirements for job tasks, our results suggest that not understanding English well enough to do an interview could possibly also be related to finding instructions difficult to understand in a job which could be further exacerbated by being older. The complicated relationships shown in the model for reporting low job control needs further investigation as this particular workplace psychosocial stressor has been associated with an increased risk of suicide [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Platt provides an excellent overview of these studies in his chapter in the recently published International Handbook of Suicide Prevention [3]. Individual-level studies consistently show over-representation in suicide statistics and heightened risk for non-fatal suicidal behaviour in individuals who are unemployed [4,5,6], work in unskilled jobs or jobs with poor psychosocial working conditions [7,8,9], have insecure housing [10,11] and relatively low levels of educational attainment [10,12,13]. Area-level studies produce less consistent findings, with some studies showing that relatively deprived areas (as assessed by average income, for example) have higher suicide or suicide attempt rates than more affluent areas, and others finding no such relationship [3,12,14].…”
Section: Introductionmentioning
confidence: 99%